Symmetric stacked fast binary counters based on reversible logic - Santhi, C; Moparthy Gurunadha Babu, Dr. (International Journal of Engineering and Technology, 2018)
A Symmetric Stacked Fast Binary counter design is proposed in this paper. In the circuit design, the first phase is occupied by 3-bit stacking circuits, which are further followed by combining circuits. The resultant novel circuit thus becomes a 6-bit stacker. A 6:3 counter has been chosen as an example to demonstrate the working of the proposed circuit. The proposed circuit is further implemented by using reversible logic gates. Heat dissipation is a major problem in the designing of a digital circuit. Rolf Landauer has proved that the information loss in a digital circuit is directly proportional to the energy dissipation. The proposed modified Symmetric Stacking counter is implemented using reversible logic gates thus reducing the power dissipation of the circuit.Â
Keywords: Use about five key words or phrases in alphabetical order; Separated by Semicolon.